If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 2x + -3 Reorder the terms: 3(-2 + x) = 2x + -3 (-2 * 3 + x * 3) = 2x + -3 (-6 + 3x) = 2x + -3 Reorder the terms: -6 + 3x = -3 + 2x Solving -6 + 3x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 3x + -2x = -3 + 2x + -2x Combine like terms: 3x + -2x = 1x -6 + 1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 1x = -3 + 0 -6 + 1x = -3 Add '6' to each side of the equation. -6 + 6 + 1x = -3 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = -3 + 6 1x = -3 + 6 Combine like terms: -3 + 6 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 6(2n+4)=8(6n+4)+8 | | 2(x+5)=6x-3 | | 2/3=n/21 | | 3/4-4/9 | | r-7.3=-0.2 | | x^2y^2+4xy=-3 | | 4x=16x+3 | | 10x^2+2x=12 | | 0.6x-1.5=1.4x+1.9 | | 4(3)=13x | | 50=-6+-4.5x | | 9(2n+1)=9(5n+2)+4 | | 9x+3=4w+2 | | 4(y+6)+y=3(y+2)-8 | | -3(t-1)+6t=7t-9 | | -15y=12-3x | | 11y=17(8) | | 11(12)=8x | | V^2=17v | | x(x)=x | | 7(-9-x)=-35 | | 4a+7b=15 | | 7v=8(12) | | 48y^4-8y^3= | | 8(10)=17x | | 8/17=x/10 | | -2x-y+3z=0 | | 9x^4-63x^2+54=0 | | 50=-4.5x-6 | | 8/17=x=10 | | y=-4.5x-6 | | x^2+6=30 |